2022
DOI: 10.1016/j.jcyt.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Spike-directed vaccination elicits robust spike-specific T-cell response, including to mutant strains

Abstract: Although most studies describing coronavirus disease 2019 vaccine responses have focused on antibodies, there is increasing evidence that T cells play a critical role. Here the authors evaluated T-cell responses in seronegative donors before and after vaccination to define responses to the severe acute respiratory syndrome coronavirus 2 reference strain as well as to mutations in the variant strains Alpha/B.1.1.7 and Beta/B.1.351. The authors observed enhanced T-cell responses to reference and variant spike st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…[83][84][85] Importantly, high throughput systematic analysis of CD8 + T cell activity in response to mutant peptides from SARS-CoV-2 variants of concern-including alpha, beta, and delta variants-has suggested decreased ability of some mutant epitopes to bind to certain HLA, 86,87 which highlights the need to ensure that CSTs generated for clinical use maintain activity against circulating strains as new variants arise. 72 SARS-CoV-2-specific T cells are longlasting in convalescent individuals, retaining activation and proliferation capacity ex vivo for at least 10 months, 88 and supporting the assertion that CSTs may provide durable protection against severe illness due to SARS-CoV-2, even as humoral immunity wanes. 89…”
Section: Clinical Use Of Sars-cov-2-specific T Cellsmentioning
confidence: 74%
See 2 more Smart Citations
“…[83][84][85] Importantly, high throughput systematic analysis of CD8 + T cell activity in response to mutant peptides from SARS-CoV-2 variants of concern-including alpha, beta, and delta variants-has suggested decreased ability of some mutant epitopes to bind to certain HLA, 86,87 which highlights the need to ensure that CSTs generated for clinical use maintain activity against circulating strains as new variants arise. 72 SARS-CoV-2-specific T cells are longlasting in convalescent individuals, retaining activation and proliferation capacity ex vivo for at least 10 months, 88 and supporting the assertion that CSTs may provide durable protection against severe illness due to SARS-CoV-2, even as humoral immunity wanes. 89…”
Section: Clinical Use Of Sars-cov-2-specific T Cellsmentioning
confidence: 74%
“…[67][68][69][70][71] Moreover, these spikedirected T cell responses elicited from vaccinated but previously uninfected donors against peptide pools created from the Wuhan strain, have shown cross reactivity to other variant strains thereby broadening the applicability of this approach. 72 Currently, there are seven registered phase I/II trials evaluating allogeneic CSTs for the treatment or prevention of COVID-19, four of which are actively recruiting patients (Table 1).…”
Section: Clinical Use Of Sars-cov-2-specific T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent emergence of the omicron variant, two doses of Comirnaty were reported by Pfizer to confer protection against any severe disease, although a booster dose is recommended. Since the majority of the epitopes on the S protein of the omicron variant are predicted to maintain their ability for human leukocyte antigen-epitope binding, vaccines such as Comirnaty that focus on the S protein are expected to elicit a sufficiently robust T cell immunity against VOCs such as omicron [34][35][36]. A study on the effectiveness of Pfizer's Comirnaty and Astra-Zeneca's ChAdOX1 against the delta (B.1.617.2) variant demonstrated that the efficacy of both vaccines was lower for the delta variant than for the alpha (B.1.1.7) variant [37].…”
Section: Messenger Rna Vaccinesmentioning
confidence: 99%
“…CST products can be generated not only from virus-experienced but also virus-naive donors, as SARS-CoV-2-specific T cell responses were observed in some unexposed individuals, likely due to pre-existing cross-reactivity with common seasonal coronaviruses [ 73 , 146 , 163 , 164 , 165 ]. The pool of potential donors can be also enriched with individuals vaccinated against SARS-CoV-2 [ 166 , 167 , 168 ], whose specific T cell responses have been proven effective against other virus variants [ 169 , 170 ]. The generation of CSTs from vaccinated donors on a clinically relevant scale was successfully demonstrated for the first time by Taborska et al [ 171 ].…”
Section: Large-scale Production Of Sars-cov-2-specific T-cellsmentioning
confidence: 99%